2012
DOI: 10.1242/jeb.062992
|View full text |Cite
|
Sign up to set email alerts
|

Extending food deprivation reverses the short-term lipolytic response to fasting: role of the triacylglycerol/fatty acid cycle

Abstract: SUMMARY The effects of short-term food deprivation on lipid metabolism are well documented, but little is known about prolonged fasting. This study monitored the kinetics of glycerol (rate of appearance, Ra glycerol) and non-esterified fatty acids (Ra NEFA) in fasting rabbits. Our goals were to determine whether lipolysis is stimulated beyond values seen for short-term fasting, and to characterize the roles of primary (intracellular) and secondary (with transit through the circulation) triacylgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
(69 reference statements)
1
8
2
2
Order By: Relevance
“…In subcutaneous WAT, [ 18 F]FDG uptake was increased, which may be explained by an increased triacylglycerol/fatty acid cycling, whereby α-glycerol phosphate, which provides the backbone for esterification of NEFAs, is derived from plasma glucose uptake, as demonstrated previously [35]. The energy required for this process might actually contribute to the increase in energy expenditure that we measured upon fasting [36]. In skeletal muscle, cold-induced glucose uptake was not affected by fasting; these results may indicate that even though cold exposure may not be able to increase glucose clearance under insulin-resistant conditions via BAT, the effect of cold exposure on other glucose-consuming tissues may still be worth exploring as a therapy to boost glucose clearance under insulin-resistant states.…”
Section: Discussionsupporting
confidence: 56%
“…In subcutaneous WAT, [ 18 F]FDG uptake was increased, which may be explained by an increased triacylglycerol/fatty acid cycling, whereby α-glycerol phosphate, which provides the backbone for esterification of NEFAs, is derived from plasma glucose uptake, as demonstrated previously [35]. The energy required for this process might actually contribute to the increase in energy expenditure that we measured upon fasting [36]. In skeletal muscle, cold-induced glucose uptake was not affected by fasting; these results may indicate that even though cold exposure may not be able to increase glucose clearance under insulin-resistant conditions via BAT, the effect of cold exposure on other glucose-consuming tissues may still be worth exploring as a therapy to boost glucose clearance under insulin-resistant states.…”
Section: Discussionsupporting
confidence: 56%
“…Several authors demonstrated an increase of lipolysis and NEFA concentrations during fasting in non pregnant rabbits (Brecchia et al, 2006;Weber and Reidy, 2012). However, there was no complete food deprivation in our experiment and moreover, the energy balance of the first week of rabbit pregnancy is positive because the requirements for foetal growth are relatively small (Fortun-Lamothe, 2006).…”
Section: Groupmentioning
confidence: 53%
“…Despite stable whole body lipolysis rates, NEFA increased across the fast (similar to our study), suggesting a possible decrease in re-esterification from early to late lactation (Houser ). Reductions in rates of re-esterification with prolonged fasting have also been reported in rabbits (Weber and Reidy 2012) and are suggested in fasting elephant seal weanlings (Viscarra et al 2012). While re-esterification rates are not known in lactating elephant seals, it seems possible that they may play a role in the uncoupling of whole body lipolysis from plasma NEFA concentrations.…”
Section: Regulation Of Hsl and Atglmentioning
confidence: 88%